(untitled) (International Journal of Engineering and Computer Science, 2017)
Damages caused by the past earthquake have pointed out that the seismic behavior of a structure not only depends upon the response of the super structure but also depend upon the response of the foundation and sub soil. The soil structure interaction effect is prominent for massive structures resting on relatively soft soil, layered subsoil such as high-rise buildings, nuclear power plants and elevated highways. The soil structure interaction effect is prominent for massive structures resting on relatively soft soil, layered subsoil such as high-rise buildings, nuclear power plants and elevated highways. Soil structure interaction is one of the major subjects of earthquake engineering and has been paid more attention in recent decades.